2015
DOI: 10.1155/2015/935309
|View full text |Cite
|
Sign up to set email alerts
|

Enabling 4-Lane Based 400 G Client-Side Transmission Links with MultiCAP Modulation

Abstract: We propose a uniform solution for a future client-side 400 G Ethernet standard based on MultiCAP advanced modulation format, intensity modulation, and direct detection. It employs 4 local area networks-wavelength division multiplexing (LAN-WDM) lanes in 1300 nm wavelength band and parallel optics links based on vertical cavity surface emitting lasers (VCSELs) in 850 nm wavelength band. Total bit rate of 432 Gbps is transmitted over unamplified 20 km standard single mode fiber link and over 40 km link with semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…In spite of this, it may still cause penalty when jitter occurs since jitter leads to CAP constellations with not only phase rotation (can be corrected) but also with points more scattered [22]. On this point, K-mean or other nonlinear machine learning equalization schemes may offer better performance than linear MMA [31][32][33][34]. Note that equalizers alone can not address cycle slip issue.…”
Section: B Timing Recoverymentioning
confidence: 99%
“…In spite of this, it may still cause penalty when jitter occurs since jitter leads to CAP constellations with not only phase rotation (can be corrected) but also with points more scattered [22]. On this point, K-mean or other nonlinear machine learning equalization schemes may offer better performance than linear MMA [31][32][33][34]. Note that equalizers alone can not address cycle slip issue.…”
Section: B Timing Recoverymentioning
confidence: 99%
“…In [17], the multi-band approach was reported to support multi-user access network with 9.3 Gb/s/user. A number of research reports can be found in the recent literature illustrating the interest and feasibility of m-CAP for fiber infrastructures [22,23]. A novel three-dimensional (3D) m-CAP system was investigated in [24] showing the improved performance in the fiber dispersion over the conventional 3D-CAP scheme.…”
Section: Performance Analysis Of M-cap Systemsmentioning
confidence: 99%
“…Discrete Multi-tone (DMT) was shown in various flavours to be able to transmit over distances of more than 80 km and at data rates of more than 56 Gbit/s per channel [5]- [9]. Also carrierless amplitude and phase modulation (CAP) seems to be an interesting modulation format for such a scenario [10]- [13]. In addition, numerous publications showed PAM-4 as a possible modulation format for this application, allowing per channel data rates even up to 112 Gb/s [14]- [17].…”
Section: Introductionmentioning
confidence: 99%